2017
DOI: 10.1007/s10661-017-6148-3
|View full text |Cite
|
Sign up to set email alerts
|

Ecotoxicological risk assessment and seasonal variation of some pharmaceuticals and personal care products in the sewage treatment plant and surface water bodies (lakes)

Abstract: This paper reports the seasonal variation and environmental quality control data for five fingerprint pharmaceuticals and personal care products (PPCPs) (acetaminophen ciprofloxacin, caffeine, irgasan and benzophenone) in the influent and the effluent of the sewage treatment plant (STP) and surface water bodies (six major lakes) in and around Nagpur, one of the "A class city" in the central India over a period of 1 year. The target compounds were analysed using developed offline solid-phase extraction (SPE) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
17
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(28 citation statements)
references
References 87 publications
3
17
0
3
Order By: Relevance
“…Interestingly, a seasonal variation in the occurrence and concentration of pharmaceuticals in water bodies has been often recorded (Archana et al 2017), raising the question of cumulative effects of elevated temperature of the surface waters and the putative high levels of pharmaceuticals, during the hot season/summer months. Yang et al (2017) showed that the overall pharmaceutical levels both in surface water and riverside groundwater are detected at higher concentrations during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a seasonal variation in the occurrence and concentration of pharmaceuticals in water bodies has been often recorded (Archana et al 2017), raising the question of cumulative effects of elevated temperature of the surface waters and the putative high levels of pharmaceuticals, during the hot season/summer months. Yang et al (2017) showed that the overall pharmaceutical levels both in surface water and riverside groundwater are detected at higher concentrations during the dry season.…”
Section: Introductionmentioning
confidence: 99%
“…Three trophic levels (fish, daphnid, and algae) were selected in the aquatic ecosystem to calculate the RQ value (Figure 4). There is a potential high risk when the calculated RQ > 1, a medium risk when 1 > RQ > 0.1, and a low or negligible risk when 0.1 > RQ > 0.01 [36,44,45,46]. By analyzing the calculated results, only the RQ of CA detected in Plants A and D and IPF detected in Plant D were between 0.1 and 0.01, indicating a low and almost negligible hazard.…”
Section: Risk Assessment Of Ppcps In Effluentmentioning
confidence: 99%
“…In the study conducted byTran et al (2014), up to 3594 µg/L of caffeine was detected in a raw wastewater sample in Singapore[55]. A considerably high concentration of caffeine (499 µg/L) in a raw wastewater sample from India was also reported byArchana et al (2017) [87]. Both studies cited lifestyle or patterns of consumption as the primary cause of the high detection of caffeine in wastewater.…”
mentioning
confidence: 95%